Dividend omissions and intraindustry information transfers - CATON, Gary L. (Institutional Knowledge at Singapore Management University, 2003)
We examine potential information transfers from companies that announce dividend omissions to their industry rivals. Specifically, we examine the abnormal stock returns and abnormal earnings forecast revisions of rivals after a company makes a dividend-omission announcement. Our results show negative and significant abnormal stock returns and negative and significant abnormal forecast revisions for rival companies in response to the announcement, and a significant and positive relation between the two. We conclude that a dividend-omission announcement transmits unfavorable information across the announcing company's industry that affects cash flow expectations and ultimately stock prices.